1977
DOI: 10.1007/bf00231407
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscope study of the microvasculature of the avian lung

Abstract: 1. The microvasculature of the lung of the duck and pigeon was studied by scanning electron microscopy of vascular casts and critical point dried preparations of the gas exchange tissue. 2. The gas-exchange cappilaries are discrete tubular vessels intimately associated with air capillaries in a three dimensional network. 3. The capillaries originate from arteries at the periphery of the parabronchus, and are collected by veins which run close to its luminal surface. 4. The capillary bed of 3-5 atria is drained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 10 publications
3
48
1
Order By: Relevance
“…The existence of a crosscurrent arrangement of the structural components has been reported previously by Duncker (1971Duncker ( , 1974Duncker ( , 1979, Abdalla and King (1975), West et al (1977), Maina (1982Maina ( , 1988, and (Abdalla, 1989). But, while these studies were meticulously done, the techniques that were applied were not sufficiently robust to categorically explicate the highly complex spatial architecture of the exchange tissue of the avian lung.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…The existence of a crosscurrent arrangement of the structural components has been reported previously by Duncker (1971Duncker ( , 1974Duncker ( , 1979, Abdalla and King (1975), West et al (1977), Maina (1982Maina ( , 1988, and (Abdalla, 1989). But, while these studies were meticulously done, the techniques that were applied were not sufficiently robust to categorically explicate the highly complex spatial architecture of the exchange tissue of the avian lung.…”
Section: Introductionsupporting
confidence: 71%
“…The structure and the arrangement of the air-and the blood-conducting components in the parabronchus of the Ostrich lung, especially concerning lack of interparabronchial septa and presence of shallow atria and poorly developed atria muscles, resembles some of those reported in the lungs of the many bird species studied by Duncker (1974), the Khaki Campell Duck (Anas platyrhynchos) and the Homing Pigeon (Columba livia) investigated by West et al (1977) and the Domestic Fowl (Gallus gallus variant domesticus) examined by Abdalla and King (1975), Brackenbury and Akester (1978), Fujii et al (1981), and Maina (1982Maina ( , 1988. Maina et al (1982) observed that the atria, interatrial septa, and atrial muscles are poorly developed in the relatively smaller and more metabolically active passeriform, columbiform, cuculiform, and psittaciform taxa of birds but well-formed in the galliforms, anseriforms, and charadriiforms.…”
Section: Computer Reconstruction Of Parabronchus Of Ostrichmentioning
confidence: 61%
See 2 more Smart Citations
“…The elastic tissue fibers may act as energy-storing elements in opposition to the intrinsic tone of the smooth muscle fibers, and the collagen fibers may limit the stretchability of the contractile components. McLelland (1989) described the orientation of the atrial septa as that of a 'shallow-pitched helix, and King & Cowie (1969), Gerisch &Schwartz (1972), andWest et al (1977) observed that the larger atrial muscles form an angle of 60-70°, whereas the smaller ones form an angle of 45°to the long axis of the parabronchus; the strut-like oriented atrial muscles may provide linear stiffening and efficient dissipation of Contraction of the atrial smooth muscles exerts a pulling force directed towards the center of the parabronchial lumen (the arrows of the springs projecting into the parabronchial lumen). The pull is transmitted to the elastic fibers (shown by the springs) in the interatrial and the interinfundibula septae.…”
Section: Discussionmentioning
confidence: 99%